Prognostic outcome of cervical laser ablation using a holmium yttrium-aluminum-garnet (Ho:YAG) laser for the treatment of cervical intraepithelial neoplasia: A single-center retrospective study - Wataru Suzuki; Kana Ietani; Takeshi Makabe; Shinya Oki; Akiko Ohno; Yoshiko Mikami; Hiroshi Yamashita (Elsevier, 2024)
Objective: Although cervical conization is considered a standard treatment for cervical intraepithelial neoplasia (CIN) 2/3, laser ablation can compensate for the disadvantages of the former. CO2, semiconductor, and holmium yttrium-aluminum-garnet (Ho:YAG) lasers are applied in ablation, but no previous studies have shown the effectiveness of any of these techniques. Here, we retrospectively analyzed the application of the Ho:YAG laser in our hospital to verify its efficacy, and discussed the methods for optimal recurrence detection. Methods: We evaluated the recurrence rates of the pathological condition in patients who underwent laser ablation with a Ho:YAG laser for CIN2/3 at our institution from June 2012 to November 2021. We defined the recurrence as histologically confirmed CIN2 or more advanced stage. Age, preoperative diagnosis, human papillomavirus (HPV) genotype, and postoperative high-risk HPV status were recorded to establish their association with recurrence rates. Results: We performed surgery in 607 patients and the 2-year recurrence rate after interventions was 5.6%. Five patients were diagnosed with invasive cancer at the time of recurrence. Older age significantly correlated with higher risk of recurrence, but preoperative CIN grade and preoperative HPV 16/18 status did not significantly affect it. The postoperative high-risk HPV test was 100% sensitive for detecting recurrence. Conclusions: Laser ablation with the Ho:YAG laser yields promising results. Together with postinterventional management, high-risk HPV test after laser ablation should be conducted after diagnostic conization.This study received the approval from the Ethics Committee of the NHO Tokyo Medical Center (Ethics Committee approval number: R22-067).